Leadership and curriculum innovation through semesterization: a case study from Portugal - Silva, Sofia; Fraga, Nuno; Andrade, Ricardina; Venâncio de Vasconcelos, Mafalda (Frontiers in Education, 2026)
IntroductionThe organization of school time plays a decisive role in shaping teaching practices, student learning, and school culture. In Portugal, semesterization has emerged as an alternative to the traditional trimester system, aiming to improve curriculum coherence and pedagogical depth. This study examines how semesterization was interpreted and implemented in a public lower secondary school in Madeira, and how educators perceived its impact on organizational functioning and teaching practices. Recent scholarship highlights that time-use reforms such as semesterization are more likely to succeed when mediated by adaptive and distributed leadership and supported by coherent policy.MethodsA qualitative-dominant mixed-methods case study design was adopted. Data were collected through semi-structured interviews with school leaders and an online questionnaire completed by 41 teachers from different subject areas. The qualitative component was analyzed using thematic content analysis, identifying patterns related to leadership, curriculum organization, pedagogical adaptation, and assessment practices. Descriptive statistics from the questionnaire were used to complement qualitative insights, providing an overview of broader staff perceptions.ResultsParticipants perceived that semesterization contributed to a more coherent distribution of teaching time, supported thematic planning, and facilitated a steadier pedagogical rhythm for both teachers and students. Teachers described enhanced opportunities for interdisciplinary collaboration, more intentional curriculum mapping, and increased space for formative assessment. A majority also reported positive effects on student well-being. However, challenges were noted, including the substantial effort required to redesign planning tools, persistent bureaucratic demands, and concerns about achieving consistency in assessment practices across semesters. Teachers also highlighted increased workload during reporting periods, particularly in relation to mandatory mid-semester qualitative feedback.DiscussionThe findings suggest that semesterization can act as a lever for school-wide innovation when supported by distributed leadership, collaborative planning structures, and clear communication. At the same time, the reform’s success depends on system-level coherence and adequate institutional support during periods of transition.ConclusionSemesterization represents not merely a scheduling adjustment but a strategic rethinking of time as an organizational and pedagogical resource. The case offers transferable insights for education systems aiming to build more coherent, equitable, and learner-centered environments.